Territorial subjectivities: the missing link between political subjectivity and territorialization - Schwarz, Anke; Streule, Monika (Progress in human geography, 2024)
Political subjectivity and territorialization often appear disconnected in recent debates. We propose a fresh approach based on Latin American scholarship to understand subjects and territories as relational: Subjects are (de)stabilized in processes of territorialization, while territories are (de)stabilized in processes of subject formation. We introduce the concept of territorial subjectivities and use examples from the literature to show how these emerge in Berlin, Buenos Aires, and Dresden. Placing an analytical focus on becoming rather than being, the contingency of territorial subjectivities is key to this novel conceptual link that supports a differentiated reading of socio-territorial struggles in diverse geographical contexts.
Gesehen am 09.08.2024
First published online January 23, 2024